Guidebook on monitoring and evaluation of programmes/projects - Mercado, Cesar M. (Quezon City Development Consultants for Asia Africa Pacific, 2003)
Purpose: "...discusses Monitoring and Evaluation (ME), the most neglected functions in programme/ project management." : target audience - programme/project managers, trainors and monitoring and evaluation staff of development projects.
Personal experiences of the author on Monitoring and Evaluation mostly in Asian countries -- Programme/project management -- Samples of monitoring forms -- Evaluation questionnaires -- KASP.
Keywords: Industrial project management -- Evaluation -- Handbooks, manuals, etc